Economic security of Ukrainian regions: pre-war and war periods - Liubov Kovalska; Olena Zavadska (Research on Enterprise in Modern Economy Theory and Practice)
Background and Objective: The relevance of the research lies in the need to in ensuring the economic security of the regions of Ukraine in the pre-war and war periods. Martial law conditions have a negative impact on the state of economic security at different levels of governance: micro, meso and macro levels and limits the processes of ensuring national competitiveness. The purpose of the study is to assess the trends in ensuring the economic security of the regions of the State in the pre-war and wartime periods.